METODE TUTOR SEBAYA DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA - Ahda Nst, Haryati; dalilah, Nur (EDUTECH CONSULTANT, 2019)
This study aims to determine whether there is an increase in students' cognitive learning outcomes by applying the peer tutoring method. This type of research is a kind of quasi-experimental research design with pretest posttest control group design. This study has two types of variables, namely the independent variable and the dependent variable. Where the independent variable is the peer tutoring method and the conventional method while the dependent variable in this study is mathematics learning. The population of this study is all eighth grade students of SMP Negeri 1 Simpang Empat. The research sample was class VIII-3 (control class) and class VIII-4 (experimental class). The instrument used is a test, then the data is analyzed by t test. Based on the t test obtained thitung = 2.400> t table = 2.03 or a significance value of 0.000 <0.05 means that H0 is rejected. This means that there is an increase in cognitive learning outcomes of students by applying the peer tutoring method.